Arthroscopic autologous chondrocyte implantation in the hip for the treatment of full-thickness cartilage defects: a case series of 29 patients and review of the literature - Thier, Steffen; Weiß, Christel; Fickert, Stefan (SICOT-J, 2017)
PURPOSE: Current literature indicates that the appropriate treatment of articular cartilage defects has significant influence on the postoperative outcome after hip arthroscopy. In the hip, arthroscopic treatment of cartilage defects is technically challenging, especially the autologous chondrocyte implantation/matrix-associated autologous chondrocyte implantation (ACI/MACI) procedures. The purpose of this prospective study was to introduce two injectable MACI products with self-adherent properties. Furthermore, we report short-term outcome and review the current literature. METHODS: Full-thickness cartilage defects of 29 patients caused by the femoroacetabular impingement (FAI) were treated arthroscopically with an injectable MACI product in a two-step surgical procedure. The patient-related outcome was assessed with International Hip Outcome Tool (iHOT33), Euro-Quol group score (EQ-5D) and Non-Arthritic-Hip-Score (NAHS) at baseline, six weeks, six, 12 and 24 months. RESULTS: Twenty-nine out of 46 patients (27 male/two female) with a mean age of 30.3 years (range 18-45 years) and an average defect size of 2.21 cm2 were available for follow-up after a mean of 19 months (range 6-24 months). All defects were located on the acetabulum International Cartilage Repair Society (ICRS) grade 3A-3D (nine 3A; eleven 3B; six 3C; three 3D). Twenty-six patients had associated labral pathology (23 repair 1-5 anchors; three partial trimming). Twenty-seven defects were caused by the FAI (20 CAM, six combined, one Pincer), two cases were of traumatic cause. An overall statistically significant improvement was observed for all assessment scores at an average follow-up of 19 months. CONCLUSION: In this study, we present short-term data of new arthroscopic injectable matrix-associated, autologous chondrocyte implants as a treatment option for full-thickness cartilage defects of the hip. All patient-administered assessment scores demonstrated an increase in activity level, quality of life and reduction of pain after a 19-month follow-up. Further randomized controlled trails (RCTs) with comparison of natural history, bone marrow stimulation techniques and MACI of the hip have to approve the results in long-term follow-up.
Gesehen am 23.04.2018